Transgeneridade, mídia e consumo: um estudo de caso das visibilidades midiáticas de Laerte Coutinho - Theodoro, Hadriel Geovani da Silva (2016)
With the prospect of contributing towards reflections and social practices regarding the politics of media visibility and citizenship for transgendered people, this dissertation articulates studies in the areas of gender and sexuality, communication, media, and consumption. The main objective is to analyze the media visibility of transgendered people in the context of a contemporary consumption society, starting from a case study of the experiences of Laerte Coutinho, cartoonist and nationally renowned activist. The theoretical framework is guided by authors from queer studies, cultural studies, and media and consumption theory. The research methodology, of a qualitative nature, is based on the analysis of a corpus made up of eight items from the media, in addition to an interview carried out with Laerte and an observation of her personal page on the social media network, Facebook. The results of the analysis point to the maintenance of stereotyped, or even prejudiced, frames as related to the visibility of Laerte s transgenderedness, particularly in traditional mass media. In relation to counter-hegemonic or alternative media and social networking spaces, especially on the cartoonist s Facebook profile page, these frames are more favorable towards the policies of visibility for transgenderedness. Finally, the path of the analysis points out difficulties and limits in constituting the politics of media visibility for transgenderedness that promote an effective shift away from a gender binary in our society and culture.